Political self-identification of the middle class in tropical Africa – the opinion of African students in Ukraine - Олійник, Ю. І. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2016)
The article presents the results of the research – questionnaires of students from the African countries. Research results allow us to make certain suppositions about the level of loyalty to the government in different ethnic and religious groups and the feeling of discrimination among the minorities.